2015
DOI: 10.33549/physiolres.932723
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Weight Reduction on Plasma Leptin and Adiponectin/Leptin Ratio in Obese Patients With Type 1 Diabetes Mellitus

Abstract: The aim of this study was to explore the changes in the adipokines leptin and adiponectin in obese patients with type 1 diabetes mellitus (T1DM) who underwent seven days of fasting and 21 days of low-calorie diet (LCD). The plasma leptin and adiponectin concentrations were measured in 14 obese patients with T1DM at baseline, immediately after 7 days of fasting, and after 21 days of LCD. 13 non-obese patients with T1DM were studied only after an overnight fasting. Bioimpedance technique was used for determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
3
1
Order By: Relevance
“…Studies in STZ-diabetic rats have indicated that the levels of serum Leptin and Leptin mRNA noticeably diminished (28). The levels of plasma Leptin also decreased in Type II DM patients (30) and in Type I DM patients (31). In our study, although Leptin levels in STZ group were lower than the control group, this was not statistically significant (p = 0.055).…”
Section: Discussioncontrasting
confidence: 82%
“…Studies in STZ-diabetic rats have indicated that the levels of serum Leptin and Leptin mRNA noticeably diminished (28). The levels of plasma Leptin also decreased in Type II DM patients (30) and in Type I DM patients (31). In our study, although Leptin levels in STZ group were lower than the control group, this was not statistically significant (p = 0.055).…”
Section: Discussioncontrasting
confidence: 82%
“…The improvements in the levels of adiponectin and leptin, analyzed independently, were not significant; however, the A/L ratio did obtain a significant increase after the training period ( p = 0.009), with a large effect size (0.53). The A/L ratio is a biomarker that has been well studied in its relationship with lipoinflammation [ 16 ], and as an indicator of obesity and metabolic risk [ 46 , 47 , 48 ]. However, only few studies have analyzed the effect of planned and controlled physical exercise programs on this marker (A/L ratio) in people with obesity, and most of these studies evaluated these two adipocytokines independently [ 27 , 30 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies including ours (unpublished data) demonstrate that mean leptin levels in prepubertal, lean and obese female, male children vary and correlate with Body Mass Index (BMI) [10]. Musil et al [11] recently examined the influence of leptin, adiponectin in obese patients with Type I diabetes after 7 days of fasting or 21 days of low calorie diet and reported that fasting significantly reduced the hyper leptinemia in Type 1 diabetes patients [11]. Other interesting studies have also brought forward that type 1 diabetes subjects with homozygotic variants in leptin gene (-2548 G/A) and leptin gene receptor (668 G/A) exhibit significant variations in leptin influenced fetal weight, growth in the first trimester [12].…”
Section: Influence Of Leptin In Obesity and Type I Diabetesmentioning
confidence: 68%